Development of Clinical Practice Guidelines for the Prevention of Early Postpartum Hemorrhage in Mothers at Pakchom Hospital, Loei Province - Sornkaew, Uriwan (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This developmental research aimed to develop clinical practice guidelines for the prevention of early postpartum hemorrhage within the first 24 hours after delivery among mothers giving birth at Pakchom Hospital, Loei Province. The study involved a committee of 9 members for guideline development, 12 guideline users, and 48 postpartum mothers. The research instruments included questionnaires, clinical practice guidelines, and an evaluation form for guideline implementation. Data were collected using questionnaires and by assessing compliance with the guidelines. Descriptive statistics and content analysis were employed for data analysis. The findings revealed that the developed guidelines encompassed 6 aspects based on the JCAHO framework: protection of the rights of mothers giving birth, maternal health assessment, prevention of hemorrhage, provision of education, continuity of care, and improvement of service quality. Following the implementation of the guidelines, the rate of early postpartum hemorrhage decreased from 6.95% in 2020 to 3.79% in 2023. The main causes were uterine atony (83.33%) and birth canal injuries (16.67%). The feasibility assessment of the guidelines showed that users rated them highly in terms of ease of implementation (75%), appropriateness of content (66.67%), resource efficiency (58.33%), and benefits to mothers giving birth (75%), indicating the feasibility of their practical application.